2013
DOI: 10.1096/fj.12-214056
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 and presenilin/γ‐secretase regulate proteolytic processing of KCNE1 and 2, auxiliary subunits of voltage‐gated potassium channels

Abstract: BACE1 and presenilin (PS)/γ-secretase play a major role in Alzheimer's disease pathogenesis by regulating amyloid-β peptide generation. We recently showed that these secretases also regulate the processing of voltage-gated sodium channel auxiliary β-subunits and thereby modulate membrane excitability. Here, we report that KCNE1 and KCNE2, auxiliary subunits of voltage-gated potassium channels, undergo sequential cleavage mediated by either α-secretase and PS/γ-secretase or BACE1 and PS/γ-secretase in cells. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…This work confirms a recent report of mild interneuron dysfunction associated with early-to-mid-level amyloid pathology, whereby neocortical interneurons had reduced action potential amplitude and this could be rescued with overexpression of Nav1.1 in the inhibitory cells [21]. Alternatively, there have been other channelopathies that have been reported to be disturbed in mouse models of aging and AD, including potassium [66], calcium and calcium-dependent potassium channels [67], [68] and muscarinic M current [69]. Our current results reveal that there is a broad degree of hyperexcitability within the dentate gyrus, the hippocampal circuits and that at the advanced stages of Aβ pathology interneuron ability to generate action potentials may be completely lost.…”
Section: Discussionsupporting
confidence: 90%
“…This work confirms a recent report of mild interneuron dysfunction associated with early-to-mid-level amyloid pathology, whereby neocortical interneurons had reduced action potential amplitude and this could be rescued with overexpression of Nav1.1 in the inhibitory cells [21]. Alternatively, there have been other channelopathies that have been reported to be disturbed in mouse models of aging and AD, including potassium [66], calcium and calcium-dependent potassium channels [67], [68] and muscarinic M current [69]. Our current results reveal that there is a broad degree of hyperexcitability within the dentate gyrus, the hippocampal circuits and that at the advanced stages of Aβ pathology interneuron ability to generate action potentials may be completely lost.…”
Section: Discussionsupporting
confidence: 90%
“…We have found that BACE1 and PS/γ-secretase cleavages of Na v β2 release a Na v β2-ICD, which modulates the levels of the pore-forming Na v 1.1 α-subunit intra-cellularly and on the cell surface [108]. Since four auxiliary subunits of the voltage-gated potassium channel are also cleaved by BACE1 and PS/γ-secretase [175], it appears that these two enzymes are involved in the regulation of ion channel function. Interestingly, voltage-gated sodium and potassium channels together are the key components of action potential generation and propagation.…”
Section: Physiological Effects Of Ps/γ-secretase-mediated Cleavage Ofmentioning
confidence: 99%
“…In addition to previously identified BACE1 substrates such as neuregulin-1 (Nrg1) (Fleck et al, 2013; Hu et al, 2008; Hu et al, 2006; Luo et al, 2011; Willem et al, 2006), voltage-gated channel proteins such as sodium channel protein β-subunits (Kim et al, 2007; Kim et al, 2011; Wong et al, 2005), the potassium channel proteins KCNE1 and 2 (Hitt et al, 2010; Sachse et al, 2013), neural cell adhesion molecule close homolog of L1 (Hitt et al, 2012; Kuhn et al, 2012; Zhou et al, 2012), Notch ligands Jagged-1 and Jagged-2 (He et al, 2014; Hu et al, 2013), and contactin-2 (Gautam et al, 2014), many more membrane-bound proteins have now been identified as BACE1 substrates by unbiased proteomic or secretome approaches using BACE1-null mouse or zebrafish models (Hemming et al, 2009; Hogl et al, 2011; Hogl et al, 2013). By comparative proteomic analyses of wild-type vs .…”
Section: Brief Overview Of Bace1mentioning
confidence: 99%